2009
DOI: 10.2174/1874210600903010042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oral Mucosal Lesions in 598 Referred Iranian Patients

Abstract: The mucosal membrane of the oral cavity displays at times classical developmental lesions considered to be variations of normal structures rather than having disease characteristics. Of these lesions leukoedema, Fordyce granules, geographic-, fissured- and hairy tongue, median rhomboid glossitis and lingual varices were studied in 598 patients referred to the School of Dentistry, Tehran, Iran. The prevalence was studied in relation to age, gender, occupation, education, smoking habits, general health, addictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
35
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 31 publications
6
35
2
8
Order By: Relevance
“…This finding is in line with other studies including Jahanbani et al (2009) who reported a positive relationship between some oral developmental lesions including Fordyce's and age and they expressed their opinions as that oral lesions exist since birth or may evident in later life.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with other studies including Jahanbani et al (2009) who reported a positive relationship between some oral developmental lesions including Fordyce's and age and they expressed their opinions as that oral lesions exist since birth or may evident in later life.…”
Section: Discussionsupporting
confidence: 91%
“…Siyah kıllı dilli hastalarda sigara, ileri yaş, erkek cinsiyet, kötü ağız hijyeni, genellikle antibiyotik, antipsikotik, antiasit gibi ilaçların kullanımı, kserostomi, kanser, trigeminal nevralji, bazı maddelerin kötüye kullanımı (kokain vb. ), oksitleyici ajan içeren ağız gargaraları (sodyum peroksit, hidrojen peroksit), edinsel immun yetmezlik sendromu tetikleyici durumlardır 1,5,[10][11][12][13][14] . Yapılan bazı çalışmalar, sigara kullanımındaki artışla doğru orantılı olarak siyah kıllı dil sıklığında da artış olduğunu göstermiştir 15,16 .…”
Section: Discussionunclassified
“…Literatür verileri incelendiğinde, cinsiyetler ve yaş grupları arasındaki farklı-lıkları araştıran çalışmalarda fissüre dil, rekürren aftöz ülser ve travmatik ülserin kadınlarda, 1 fissüre dil ve kıllı dilin erkeklerde, Fordyce granüllerini-nin 50-59 yaş arasında, erkeklerde kadınlara göre daha sık olduğu, fissüre dilin en sık 60 yaş üzerinde ancak kadın ve erkeklerde benzer prevalansta saptandığı görülmektedir. 24,30 Ayrıca lökoödemin en sık 60 yaş üstü erkeklerde, herpes enfeksiyonu ve Fordyce granüllerinin 0-15 yaş arasında, makroglossinin 60 yaş üzerinde sıklıkla tespiti gibi birbirinden çok farklı olan bulgular da dikkati çekmektedir. 3,30 Birçok çalışmada bu sonuçların irdelenmediğini, belirgin farklılıkların nedenini ortaya koyabilecek görüşlerin öne sürülmediğini görmekteyiz.…”
Section: Discussionunclassified
“…24,30 Ayrıca lökoödemin en sık 60 yaş üstü erkeklerde, herpes enfeksiyonu ve Fordyce granüllerinin 0-15 yaş arasında, makroglossinin 60 yaş üzerinde sıklıkla tespiti gibi birbirinden çok farklı olan bulgular da dikkati çekmektedir. 3,30 Birçok çalışmada bu sonuçların irdelenmediğini, belirgin farklılıkların nedenini ortaya koyabilecek görüşlerin öne sürülmediğini görmekteyiz. Daha önce de değindiğimiz gibi, ça-lışmaların metodolojilerindeki farklılıklar birbiri ile çelişir nitelikteki bu bulguların kısmen de olsa açıklayıcısı olabilir.…”
Section: Discussionunclassified
See 1 more Smart Citation